Research on the enhanced biological nitrogen removal of wastewater by the ultrasound‐hydrolysis acidification of excess sludge. (11th December 2020) - Wang, Yonglei; Liu, Yulei; Tian, Liping; Xu, Xuexin; Liu, Yongjian; Qin, Yao
Abstract: To simultaneously improve the removal of nitrogen and phosphorus from wastewater with a low C/N ratio and reduce excess sludge production, in this paper, excess sludge ultrasound‐hydrolysis acidification (UHA) pretreatment was coupled with the anaerobic–anoxic–oxic (AAO) process to provide carbon source and enhance biological nitrogen removal performance, and the experimental results can be summarized as follows. First, the total nitrogen (TN) concentrations in the effluent of the system decreased from 16.94 mg/L to 5.74 mg/L, and the removal rate of TN increased by 25.5%. In addition, the concentrations for ammonia nitrogen (NH3 ‐N) in the system decreased 12.59 mg/L, and the removal rate of this index increased by 29.0%. Furthermore, the specific oxygen uptake rate (SOUR) in the anoxic zone increased significantly because the application of UHA products enhanced the microbial activity, and the addition of UHA products had an effect on the microbial community structure in the system. The amounts of denitrifying bacteria such as Betaproteobacteria and Alphaproteobacteria also increased, which enhanced the nitrogen removal efficiency of wastewater biological treatment. Practitioner points: Treatment of excess sludge in UHA device as an additional carbon source. Nitrogen removal efficiency was greatly improved after adding UHA products. Input of UHA products enhanced microbial activity in AAO system. Denitrifying bacteria increased with the addition of UHA products. Abstract : The figure below is the graphical abstract of this paper. The excess sludge is treated by UHA, and the UHA product is returned to anoxic tank as carbon source.